MEASURING GLOBALIZATION IN THE CONTEXT OF TRANSITION PROCESS - THE CASE OF WESTERN BALKAN COUNTRIES - Jelena Tešić (Economic Review)
There is no widely accepted definition or methods for measuring globalization and it is one of the most debatable phenomena in recent human history. The focus of this paper is,  therefore, on globalization and methods of its measurement. The issue of measuring globalization inevitably involves numbers, and with the numbers one should always be careful, especially when dealing with something so complex and undefined. Also, the interpretation of results obtained by measuring globalization always requires additional interpretation. In this paper we examine the methods of measuring globalization from the macro aspect, i.e. at the level of countries, as well as the analysis of level of globalization in Western Balkan countries. As there is still an ongoing transition process in these countries, the application of globalization indices must be assessed in the overall context and complexity of transition process. The ultimate aim of this paper is to determine how to read and interpret globalization indices (indicators), and their informative power, as well as shortages in the case of transition countries such as the Western Balkans. Our results indicate that Western Balkan countries are not making sufficient progress in the transition process and they are thus not competitive. Therefore, a high degree of globalization does not imply that our countries a priori obtain the positive effects of globalization. We will try to define which additional indicators should be used when interpreting indicators of globalization for the countries of the region. The rationale behind this endeavor is the fact that the process of globalization and the process of transition present two interrelated processes for the countries of the region.